Graphic Styles Appearance In Educational Games To Enhance Malaysian Students Learning: A Preliminary Study - Lee, Lilian Shiau Gee; Dolah, Jasni (2016)

(untitled)
Research on educational games has resulted to the increase in understanding of visual design elements in game development. The effectiveness of the graphic styles presentation in an educational game also benefited students in their learning process. This paper is intended to make an initial survey and discuss how graphic styles, learning and student involvement are inexorably linked. Interviews and questionnaires were conducted to identify the importance of graphic elements needed to conduct in the development of educational games. 39 respondents were selected to participate in this preliminary study ranging from an expert in games from Universiti Malaysia Sabah (UMS), two game developers, a teacher with ICT background, two high schools teachers and 30 Form one students. Preliminary study have shown that the educational games research in Malaysia is still less pressing in visual design aspect especially in terms of graphic styles which can be implicated in educational games and to enhance Malaysian students learning